2015
DOI: 10.1016/j.amjsurg.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability analysis is more sensitive at identifying neonatal sepsis than conventional vital signs

Abstract: Background Sepsis remains the largest preventable source of neonatal mortality in the world. Heart rate variability (HRV) analysis and noninvasive cardiac output, have been shown to be useful adjuncts to sepsis detection in many patient groups. Methods With IRB approval, 4 septic and 6 nonseptic ELBW patients were enrolled. Data from septic and healthy patients were collected for 5 hours. ECG waveform and traditional vital signs were collected and the RR intervals were calculated, then heart rate variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 39 publications
4
43
0
3
Order By: Relevance
“…Probably the most advanced clinical applications of HRV can be found in neonatal intensive care medicine, in which HRV analysis has already been shown to add independent information to clinical signs scores and to allow for earlier diagnosis of neonatal sepsis. 7,26 Randomized clinical trials have revealed that heart rate characteristics monitoring can reduce the mortality rate in very low-birth weight infants 27 and is associated with a lower septicemia-associated mortality. 28 The main novel finding of this study is that the HRV is affected by even a moderate porcine sepsis without organ failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably the most advanced clinical applications of HRV can be found in neonatal intensive care medicine, in which HRV analysis has already been shown to add independent information to clinical signs scores and to allow for earlier diagnosis of neonatal sepsis. 7,26 Randomized clinical trials have revealed that heart rate characteristics monitoring can reduce the mortality rate in very low-birth weight infants 27 and is associated with a lower septicemia-associated mortality. 28 The main novel finding of this study is that the HRV is affected by even a moderate porcine sepsis without organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…Depression of heart-rate variability (HRV) in conditions of systemic inflammation has been repeatedly shown in both patients [6][7][8][9][10] and experimental animal models. [11][12][13] In some studies, a predictive power of HRV was documented, in which depression of HRVderived parameters preceded the onset of overt clinical sepsis by several hours.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis was impossible due to heterogeneity between studies with respect to the assessment of both HIE and HRV. Many of the comparisons presented in this review were not controlled for important variables such as gestational age, birth weight, and different pathological conditions e.g., malformations and sepsis [54][55][56][57]. It is well known that these factors may depress HRV measures and thereby influence the results [54][55][56][57].…”
Section: Limitationsmentioning
confidence: 99%
“…HRV features together with quantification of general physical movements have also been found useful for 2-year outcome prediction in [7]. In [8], time-domain HRV measurements have showed a significant difference between septic and nonseptic newborns. Decreased HRV was observed in children born with low birth weight, including preterm babies [9].…”
Section: Introductionmentioning
confidence: 99%